The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4103/joacp.joacp_349_15
|View full text |Cite
|
Sign up to set email alerts
|

Action and resistance mechanisms of antibiotics: A guide for clinicians

Abstract: Infections account for a major cause of death throughout the developing world. This is mainly due to the emergence of newer infectious agents and more specifically due to the appearance of antimicrobial resistance. With time, the bacteria have become smarter and along with it, massive imprudent usage of antibiotics in clinical practice has resulted in resistance of bacteria to antimicrobial agents. The antimicrobial resistance is recognized as a major problem in the treatment of microbial infections. The bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
466
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 689 publications
(560 citation statements)
references
References 27 publications
(39 reference statements)
4
466
0
17
Order By: Relevance
“…Although there were some minor increases in the zones of inhibition for the TE exposures, none of these treatments were significant enough to provide a change in susceptibility, indicating that the change in antibiotic susceptibility was due to the effects of the E-field and not to any induced heating. Although the different classes of antibiotics work on various cellular targets to inactivate bacteria (Li et al 2015;Kapoor et al 2017), the first step in the mechanism of action for all antibiotics is to traverse the cell membrane and enter the cytoplasm (James et al 2009;Krause et al 2016). Research conducted by Pillet et al (2016) showed scanning electron, transmission electron and atomic force microscopy results demonstrating the morphological, mechanical and physical damage to the cell wall of Bacillus pumilus from various strengths of µs electric pulses (Pillet et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although there were some minor increases in the zones of inhibition for the TE exposures, none of these treatments were significant enough to provide a change in susceptibility, indicating that the change in antibiotic susceptibility was due to the effects of the E-field and not to any induced heating. Although the different classes of antibiotics work on various cellular targets to inactivate bacteria (Li et al 2015;Kapoor et al 2017), the first step in the mechanism of action for all antibiotics is to traverse the cell membrane and enter the cytoplasm (James et al 2009;Krause et al 2016). Research conducted by Pillet et al (2016) showed scanning electron, transmission electron and atomic force microscopy results demonstrating the morphological, mechanical and physical damage to the cell wall of Bacillus pumilus from various strengths of µs electric pulses (Pillet et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For years, antimicrobial photodynamic therapy (aPDT) has been used effectively in the eradication of gram-positive and gram-negative bacteria [6,7]. Various bacterial cells' structures and components are the targets for PDT in contrast to one major target in the case of antibiotics [8,9]. Thus, PDT reduces the risk of developing resistance of microorganisms exposed to it [10].…”
Section: Introductionmentioning
confidence: 99%
“…Over time this leads to selection of resistant organism, the use of the antimicrobial resulting in 'selection pressure' for resistance. Although this may seem complicated, it is a simple Darwinian Table 6.3 Mechanisms of resistance in bacteria (Giedraitienė et al 2011;Kapoor et al 2017 selection occurring as a result of antimicrobial use. This is the reason why antimicrobials are fundamentally different to all other medicines; they have both an individual effect (curing the infection) and a population effect (selection for resistance), and sometimes these conflict (Sandoval-Motta and Aldana 2016).…”
Section: Resistancementioning
confidence: 99%